Diseño y simulación de un protótipo de máquina serigráfica tipo carrusel - Ramírez Cadena, Karla Sara (2017)
For years ago the textile serigraphy is a printing technique used for the duplication of images on different materials, consists of passing ink through a synthetic fabric stretched to a frame (wood or aluminum), which avoids unstressed parts. This technique is known as "sweeping" is done by means of squeegee and can be repeated thousands of times without losing image definition being this part essential to the growth of the company. The project focuses on the mechanical design of a six-arm "carousel-type" silkscreen machine for six garment stations. The operator is in charge of carrying out the two supports the rotation around the axis, until the impression of each matrix is made and thus fulfilling the cycle of operation. The aim of this machine is to improve the printing system, also optimize and expedite the speed of the process. The 3d design is carried out using the software Autodesk Inventor 2016, so the geometry of the parts that make up the machine is dimensioned, and the Finite Element analysis (FEA) is carried out to the elements that support a greater quantity of loads, the same that allows to verify if the selected material is suitable to meet the needs of the company. The materials and mechanical elements used for the design have availability in the local market in this way it avoids that the acquisition value increases. In this research work a report of the total value required for its implementation is attached. Keywords: Textile serigraphy, Sweep, Silkscreen machine, Carousel